Tuning Electronic Properties of Blue Phosphorene/Graphene-Like GaN van der Waals Heterostructures by Vertical External Electric Field - Jingjing Guo; Zhongpo Zhou; Hengheng Li; Haiying Wang; Chang Liu (Nanoscale Research Letters, 2019)
Abstract The structural and electronic properties of a monolayer and bilayer blue phosphorene/graphene-like GaN van der Waals heterostructures are studied using first-principle calculations. The results show that the monolayer-blue phosphorene/graphene-like GaN heterostructure is an indirect bandgap semiconductor with intrinsic type II band alignment. More importantly, the external electric field tunes the bandgap of monolayer-blue phosphorene/graphene-like GaN and bilayer-blue phosphorene/graphene-like GaN, and the relationship between bandgap and external electric field indicates a Stark effect. The semiconductor-to-metal transition is observed in the presence of a strong electric field.